Cognitive interviews with children as a research tool for instrument validation in adapted physical activity - Nancy L. I. Spencer; Marcel Bouffard; E. Watkinson (European Journal of Adapted Physical Activity, 2020)
The development and use of instruments to assess individuals with impairments in various domains is common practice in the field of Adapted Physical Activity. Test developers and users often question the validity of their instruments and use different conceptual and/or empirical strategies for validation purposes. One validation strategy, still rarely used in the sport sciences, is cognitive interviews with participants. This study is an attempt to show the utility of cognitive interviews for instrument development with children with relevance to the field of adapted physical activity.  Specifically, we investigated the question-and-answer processes of children with impairments when responding to the Athletic Competence Domain Subscale from Harter's (1985) Self-Perception Profile for Children. Eight children with different diagnoses (ages 8-13 years) took part in cognitive interviews. The study revealed sources of validity and invalidity in the instrument. Differences and concerns in the children's comprehension of questions and interpretation of words, leading to potentially limited and varied sources of information for response production, emerged. While judgment generally appeared to be unproblematic, topic sensitivity and limited response options were a common constraint. The data obtained from this study could be used to further refine the instrument.